Is the severity of congenital heart disease associated with the quality of life and perceived health of adult patients?. Issue 9 (15th August 2005) - Moons, P; Van Deyk, K; De Geest, S; Gewillig, M; Budts, W
Abstract : Objective: To explore whether the severity of congenital heart disease is associated with the quality of life and perceived health status of adult patients. Design: Descriptive, cross sectional study. Setting: Adult congenital heart disease programme in one tertiary care centre in Belgium. Patients: 629 patients (378 men, 251 women) with a median age of 24 years. Main outcome measures: Disease severity was operationalised in terms of initial diagnosis (classification of Task Force 1 of the 32nd Bethesda Conference), illness course (disease severity index), and current functional status (New York Heart Association (NYHA) class, ability index, congenital heart disease functional index, and left ventricular ejection fraction). Quality of life was measured by a linear analogue scale, the satisfaction with life scale, and the schedule for evaluation of individual quality of life. Perceived health status was also assessed with a linear analogue scale. Results: Scores derived from the disease severity classification systems were weakly negatively associated with quality of life and health status, ranging from −0.05 to −0.27. The NYHA functional class and ability index were consistently associated with quality of life and perceived health. Conclusions: This study showed that the severity of congenital heart disease is marginally associated with patients' quality of life and perceived health. Functional status was more related to patients' assessment of their quality of life than was the initial diagnosis or illness course.